Life in Low Density Environments – Field Galaxies from z=1.0 to the Present. Issue Volume 11:Issue S319(2015) (17th August 2016) - Jørgensen, Inger; Fisher, Scott; Woodrum, Charity; Kwan, Teiler; Bieker, Jacob
Abstract: We present results on the stellar populations of bulge-dominated field galaxies at redshifts up to ≈1.0. The sample consists of non-cluster galaxies observed as part of the spectroscopic observations for the Gemini/HST Galaxy Cluster Project (GCP). Our preliminary results show that the bulge-dominated field galaxies contain younger stellar populations than cluster galaxies at similar redshifts. Future work will include photometry from Hubble Space Telescope and will be aimed at establishing the evolution of the sizes and the mass-to-light ratios for the field galaxies.